PEMBERIAN NAFKAH TERHADAP MANTAN ISTRI MENURUT PEMIKIRAN ASGHAR ALI ENGINEER - Pebri Ardiansyah; Arne Huzaimah; Napisah Napisah (Program Studi Al-Ahwal Al-Syakhshiyyah, 2021)
When a divorce occurs between a husband and wife, it creates obligations that must be obeyed by a husband and wife, and these obligations include for an ex-husband to provide a living for the ex-wife who has been divorced. according to his ability), the provision of a living is as a consolation during the 'iddah period, this is different from Asghar's opinion, which according to him, providing a living for a divorced ex-wife, not only during the 'iddah period, but until the ex-wife remarries or dies. World Regarding the provision of a living for the ex-wife, the author tries to find the subject matter that can answer the problem, namely by looking at the views of Asghar Ali Engineer regarding the provision of a living for his ex-wife, and how Islamic law reviews the views of Asghar Ali Engineer regarding the provision of a living for his ex-wife. Wife. Based on these main issues, after a theoretical study of the problems that arise, the opinion of Asghar Ali Engineer regarding the provision of a living for his ex-wife is that there are several who are entitled based on the criteria. The criteria for ex-wives who are entitled to a living from their ex-husband are women who are unable to take care of themselves (poor), women who are very old in age, women who have no family (relatives), because it is far from a sense of justice if a woman who has been divorced there is no one to provide for her. Based on QS. Al-Baqarah (2):241, which relates to providing a living for ex-wives, namely Mata'ah and Ma'ruf, the Qur'an says that they must not only be released in a good way (Ma'ruf) but supplies (Mata'ah) is also provided in a good way too.